2010
DOI: 10.1002/jcb.22532
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 and high glucose synergistically upregulate MMP‐1 expression by U937 mononuclear phagocytes via ERK1/2 and JNK pathways and c‐Jun

Abstract: Matrix metalloproteinases (MMPs) play a pivotal role in tissue remodeling and destruction in inflammation-associated diseases such as cardiovascular disease and periodontal disease. Although it is known that interleukin (IL)-6 is a key proinflamatory cytokine, it remains unclear how IL-6 regulates MMP expression by mononuclear phagocytes. Furthermore, it remains undetermined how IL-6 in combination with hyperglycemia affects MMP expression. In the present study, we investigated the regulatory effect of IL-6 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 49 publications
3
37
1
1
Order By: Relevance
“…Our laboratory showed that high glucose increased the expression of c-Jun and c-Fos, which are the major subunits of AP-1 transcription factor (Li et al 2010). Given that AP1 is a key transcription factor for MMP9 expression (Aljada et al 2001), it is most likely that high glucose stimulates MMP9 expression by increasing AP1 level.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our laboratory showed that high glucose increased the expression of c-Jun and c-Fos, which are the major subunits of AP-1 transcription factor (Li et al 2010). Given that AP1 is a key transcription factor for MMP9 expression (Aljada et al 2001), it is most likely that high glucose stimulates MMP9 expression by increasing AP1 level.…”
Section: Discussionmentioning
confidence: 95%
“…They found that although serum cholesterol, low-density lipoprotein, C-reactive protein, and carotid atheromatous plaques were reduced in patients treated with statins, CD68-positive cells were increased in atherosclerotic lesions. Furthermore, they found that the expression of IL6, a major proinflammatory cytokine expressed by macrophages (Li et al 2010), was lower in atherosclerotic plaques in patients treated with statins. This study suggests that statin treatment attenuates macrophage activation, but not the recruitment of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-6 increases matrix degradation by stimulating matrix metalloproteinase expression and promotes bone loss by increasing osteoclastogenesis and reducing osteoblast activity (34). IL-6 is promptly and highly responsive to inflammatory stimuli, as its expression rises rapidly and robustly and reaches the peak in a few hours (1).…”
Section: Discussionmentioning
confidence: 99%